2022
DOI: 10.3389/fcvm.2022.1023549
|View full text |Cite
|
Sign up to set email alerts
|

Right heart failure after left ventricular assist device: From mechanisms to treatments

Abstract: Left ventricular assist device (LVAD) therapy is a lifesaving option for patients with medical therapy-refractory advanced heart failure. Depending on the definition, 5–44% of people supported with an LVAD develop right heart failure (RHF), which is associated with worse outcomes. The mechanisms related to RHF include patient, surgical, and hemodynamic factors. Despite significant progress in understanding the roles of these factors and improvements in surgical techniques and LVAD technology, this complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 108 publications
0
20
0
Order By: Relevance
“…RVF following implantation of an LVAD is a common problem in which up to one-third of patients may require MCS [52][53][54]. Application of the ProtekDuo® cannula as a component of an RVAD system without an ML in a (dl)VxP configuration is well-documented in this patient group [55].…”
Section: Application Of Protekduo® For Vp Ecmo In Combination With Du...mentioning
confidence: 87%
“…RVF following implantation of an LVAD is a common problem in which up to one-third of patients may require MCS [52][53][54]. Application of the ProtekDuo® cannula as a component of an RVAD system without an ML in a (dl)VxP configuration is well-documented in this patient group [55].…”
Section: Application Of Protekduo® For Vp Ecmo In Combination With Du...mentioning
confidence: 87%
“…Furthermore, right heart failure is a relatively common complication following LVAD implantation, implicated in approximately 20% of cases 31 . This has been attributed to increased right ventricular preload following amelioration of left ventricular ejection fraction after LVAD implantation 32 alongside a rightwards interventricular shift disrupting right ventricle morphology due to high CF–LVAD pump speeds 33 . Moreover, RVADs are predominantly used in the short term following cardiac surgery, including LVAD implantation 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Grupper et al [ 18 ] have studied 85 adult patients with LVAD (HeartMate II and III) and reported the improvement of pulmonary hemodynamics and echocardiographic parameters after LVAD regardless of the pre-LVAD PVR. Despite the LVAD decreases the severity of MR and pulmonary pressures, RVF may occur due to increased preload, loss of the ventricular interdependence and left-sided deviation of septum with possible right ventricular dilatation and worsening of tricuspid regurgitation [ 19 ]. RVF occurred in 32.9% of our study patients and almost half of them required the right ventricular assist device (RVAD).…”
Section: Discussionmentioning
confidence: 99%